The Rise of Subscription-Driven Financial Journalism in India - Thazhethil, Bijoy Idicheriah (Digital Repository of Theses, 2026)
The role, impact, and implications of financial journalism in India, and more specifically, the societal perception and changes in journalistic quality as a result of the subscription-based model, the effect of such a change in consumer trust, and the stability and business prospects of the media organisations are discussed in this thesis. Traditional advertisement-based models have been facing challenges for many financial news portals, which has led them to look at events and paywalls to boost revenue. As advertisers are cutting their ad spends and free rivals are on the prowl, they are switching to paywall models - either soft or hard. This study examines why media outlets make the transition to such models and to what extent subscription models affect the versatility, precision, and credibility of the news published by financial news outlets. This study shows how subscription-model works well for financial journalism where readers are looking to act upon the information, as compared to general news readership. However, paywalls run the risk of limiting access to critical information to those who can pay, so it doesn’t help boost financial literacy and awareness, as identified by the journalists and media executives and verified through survey data of consumers of financial news. Observations made in this paper suggest that although subscription-funded journalism provides better content quality and enhanced trust of readers, it has challenges like a lack of willingness by the readers to be charged for content, especially in markets that have embraced free news. Besides, concerns of availability are also evident where lower-income readers are locked out of quality financial journalism. However, the improved access to low-cost internet, and real-time online payments have enabled some publishers to opt for subscriber-only model, with innovations such as pay-as-you-read news, and curated communities of readers. Thus, this thesis contributes to the investigation of digital journalism and presents specific findings for the context of Indian financial media, as well as suggestions for media companies regarding quality and accessibility in the transition to a subscription-based model. Keywords: Subscription-driven journalism, financial journalism, India, journalistic quality, readers, consumer trust, media sustainability, digital journalism, revenue models.